An open-label randomised controlled trial on the efficacy of adding intranasal fentanyl to intravenous tramadol in patients with moderate to severe pain following acute musculoskeletal injuries - Keng, Sheng Chew; Abdul Hafiz, Shaharudin (Singapore Medical Association (SMA), 2017)
INTRODUCTION